Angiomyoma presenting as a painful subcutaneous mass: a diagnostic challenge. (16th October 2014) - Kumar, Sandeep; Hasan, Roumina; Maddukuri, Satish Babu; Mathew, Mary
Abstract : Angiomyoma of the extremity is a notoriously elusive preoperative diagnosis, as the list of differentials for its described classic clinical features of a painful mobile subcutaneous mass is quite vast. Imaging features described for angiomyomas are far from being specific. On ultrasound, angiomyomas are mostly described as a well-defined solid mass lesion showing robust internal vascularity. On T2-weighted MRI they have been described as homogenous to heterogeneously hyperintense relative to skeletal muscle. We report a pathologically proven angiomyoma around the knee joint in a middle aged man, describe its clinical and imaging features, and outlay an approach in diagnosing this rare entity as a differential for painful subcutaneous mass lesions.